Review of Performance Analysis of Lithium-Sulfur Batteries for Electric Vehicles: Challenges and Future Prospects - Akri, Akri; Lidong, Andini (Science Tech Group, 2024)
The automotive sector has witnessed rapid technological advancements, particularly in developing electric vehicles (EVs), which rely heavily on batteries for energy supply. While lithium-ion batteries are the predominant choice, they face significant challenges, including low energy density and usage limitations. As a result, researchers are exploring alternative battery technologies such as lithium-air, lithium-sulfur, and all-solid-state batteries to potentially replace conventional lithium-ion batteries in electric vehicles. This review aims to compare the performance of these alternative battery types, focusing specifically on lithium-sulfur (Li-S) batteries, which have demonstrated an energy density of 2,500 Wh/kg. This surpasses the energy densities of lithium-air batteries (250-1200 Wh/kg), all-solid-state batteries (500 Wh/kg), and lithium-ion batteries (890 Wh/kg), highlighting their significance in energy storage capacity. Given their impressive energy density and increasing attention, Li-S batteries are rapidly advancing toward mass commercialization than their lithium-ion and all-solid-state counterparts. However, several challenges remain to be addressed, particularly in enhancing battery development to ensure timely integration into the market.